Influence of mild pulsed electric field conditions on the growth and protease activity of Streptococcus thermophilus - Najim, Najim Hadi (The Iraqi Journal of Veterinary Medicine, 2010)
Pulsed electric field (PEF) processing involves the application of pulses of voltage for less than one second to fluid products placed between two electrodes. Streptococcus thermophilus is an important bacterium used for the production of fermented dairy products. Objective of this study was to determine the influence of a mild PEF condition on the growth and protease activity of Streptococcus thermophilus. A range of mild pulsed electric field conditions were earlier screened by the author to arrive at an optimum overall mild pulsed electric field condition for various probiotic characteristics. Freshly thawed Streptococcus thermophilus was suspended in 0.1% w/v sterile peptone water and treated in a pilot plant PEF system. The treatment was a mild PEF condition of positive square unipolar pulse of 3 µs, pulse period of 0.5 sec. and voltage of 1 kV/cm. Control was run through PEF system but without receiving any pulsed electric field condition. Control and treated samples flow rates were kept constant at 60 ml/min. Samples were individually inoculated in lactobacillus MRS broth. Samples were plated in duplicate. Pour plates were incubated aerobically at 37°C for 3 days. Growth was determined hourly for 20 hours. The extracellular protease activity of Streptococcus thermophilus was determined by the o-phthaldialdehyde (OPA) spectrophotometric assay. Experiments were replicated three times.The control and mild PEF treated samples had the same counts of 10.97 (+/- 0.25) log cfu/ml at 0 hour. The mild PEF treated samples reached the log phase an hour earlier than control. Although at most time points, counts were within the same log cfu/ml for the control and treated samples, the mild PEF treated samples had significantly (p<0.05) higher counts compared to control for most of the time points over the 20 hours of growth. The mild PEF condition enhanced growth of Streptococcus thermophilus. Mild PEF treatment conditions had a significant influence on the protease activity of Streptococcus.thermophilus where a significant enhancement in its proteolytic activity compared to the control has been detected.